Epidemic history investigation: a new method of finding close contacts - Li, Xin; Li, Yalan; Liu, Tianjiao; Ding, Rui; Hou, Qiannan; Xiong, Liling; Du, Na; Gong, Zhaolin; Cheng, Linbo; Luo, Dan; Wei, Sumei; Yang, Xiao (Frontiers in Public Health, 2023)
Introduction Coronavirus disease 2019 has become a major global public health concern in December 2019. However, finding and excluding close contacts of COVID-19 infectors is a critical but difficult issue. This study aimed to introduce a new method of epidemiological investigation named space–time companions, which was adopted in Chengdu, China, in November 2021. Methods An observational investigation was conducted during a small outbreak of COVID-19 in Chengdu, China in November 2021. A new method of epidemiological investigation called space–time companion was adopted in this outbreak, which was defined as the one who stayed in the same spatiotemporal grid (range: 800 m * 800 m) with the confirmed COVID-19 infector for more than 10 min in the last 14 days. A flow chart was used to describe the screening process of space–time companions in detail and illustrate the space–time companion epidemic management method. Results The COVID-19 epidemic outbreak in Chengdu was effectively controlled for approximately one incubation period (14 days). After four rounds of space–time companions screening, more than 450,000 space–time companions were screened, including 27 COVID-19 infectors. Moreover, in the subsequent rounds of nucleic acid testing for all people in the city, no infected person were found proving the end of this epidemic outbreak. Conclusion The space–time companion provides a new idea for screening close contacts of the COVID-19 infector and other similar infectious diseases, which can serve as a supplement to traditional epidemiological history surveys to verify and avoid missing close contacts.